The role of psychological factors on improving work engagement among nurses - Abualruz, Hasan; Rayan, Ahmad; Al-Ghabeesh, Suhair; Fawaz, Mirna; Jaafeer, Rayan; Qutami, Batool; Alyami, Hanan (Frontiers in Psychology, 2024)
Background: Work engagement is affected by many psychological variables including emotional intelligence, psychological empowerment, and resilience that are not well-studied among nurses.Purpose: This study aims to examine the impact of emotional intelligence on the work engagement of critical care nurses, and the mediating role of resilience and psychological empowerment.Methods: A descriptive cross-sectional design was adopted in this study among 150 critical care nurses at one university hospital in Saudi Arabia. Independent t-test and correlational Work Engagement among Nurses 2 analysis were used to assess relationships between study variables. A multi-step regression model was used to assess the mediatory effect.The results showed that a statistically significant positive association exists between each of the study variables (p<0.01). The regression model showed that higher resilience (p<0.001) and psychological empowerment (p<0.001) predicted higher work engagement. The model predicted 33.3% of the changes in work engagement scores among critical care nurses.To enhance work performance and quality of care rendered at critical care units, higher emphasis should be placed on emotional intelligence and other significant psychological variables.